Pollen, grain size, loss-on-ignition, elemental and mineralogical composition, magnetic susceptibility and radiocarbon measurements in Hashilan Wetland sediment core - Reza Safaierad; Bernd Zolitschka; Morteza Djamali; Lydie M Dupont; Christoph Vogt; Roger Matthews (PANGAEA, 2023)
The proxy data reported here are measured from a sediment core collected from the Hashilan Wetland (34° 34 extquotesingle 55 N, 46° 53 extquotesingle 13 E, 1310 m a.s.l.) in the Zagros Mountains of western Iran. The core is 315 cm long (from 85 to 400 cm under the wetland surface) and was collected using a peat corer on November 10th, 2016.